Effects of Dietary Caulerpa lentillifera Supplementation On Growth Performance and Survival Rate of Milk Fish, Chanos chanos (Forsskål, 1775) - Dedi Fazriansyah Putra; Muhammadar Abdullah Abbas; Nadri Solin; Norhayati Othman (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2021)
Abstract: The study aimed to investigate the dietary supplementation effect of sea grape, Caulerpa lentillifera, on the growth performance and survival rate of milkfish, Chanos chanos (Forsskål, 1775). Two hundred fish weighing in the range of 0.20-0.25 g/ind were randomly distributed into 20 of 25 L tanks. The 0 (control), 10, 20, 30, and 40 g/kg of Caulerpa lentillifera powder was supplemented into four formulated feeds and then fed for 49 days. The result exposed that the administration of Caulerpa lentillifera powder in the diet provided a significant effect on the absolute weight gain, absolute length gain, specific growth rate, and feed efficiency (P<0,05), but there was no significant effect on survival rate (P>0,05). The optimum specific growth rate, absolute weight, absolute length and feed efficiency were found at treatment C (20 g/kg diet) with the values of 1.597±0.137 %/days, 4.47±0.08 g, 2.98±0.77 cm and 69.86±2.72 %, respectively. Regarding this result, the supplementation of sea grape (Caulerpa lentillifera) at a 20 g/kg diet is recommended to obtain the optimum growth of milkfish (Chanos chanos).Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh suplementasi pakan anggur laut Caulerpa lentillifera terhadap performa pertumbuhan dan kelangsungan hidup ikan bandeng, Chanos chanos (Forsskål, 1775). Dua ratus ikan sampel berbobot berkisar 0.20-0.25 g/ind didistribusikan secara acak ke dalam 20 tangki dengan volume masing-masing 25 L. Tepung anggur laut dengan dosis 0 (kontrol), 10, 20, 30, dan 40 g/kg ditambahkan ke dalam lima formulasi pakan dan diberi makan sebanyak 5% dari biomassa ikan dengan frekuensi 2 kali sehari selama 49 hari. Hasil penelitian menunjukkan bahwa pemberian tepung C. lentillifera dalam ransum memberikan pengaruh nyata terhadap laju pertumbuhan spesifik, bobot mutlak, panjang mutlak dan efisiensi pakan (P<0.05), tetapi tidak berpengaruh nyata terhadap kelangsungan hidup (P>0.05). Laju pertumbuhan spesifik, bobot mutlak, panjang mutlak dan efisiensi pakan yang optimum terdapat pada perlakuan C (diet 20 g/kg) dengan nilai 1.597±0.137 %/hari, 4.47±0.08 g, 2.98± 0.77 cm dan 69.86±2.72%. Berkaitan dengan hasil tersebut, disarankan penambahan suplemen anggur laut (C. lentillifera) pada pakan 20 g/kg memberikan pertumbuhan yang optimum bagi ikan bandeng (Chanos chanos).